THE RELIABILITY OF GINGIVAL CREVICULAR BLOOD AS A DIAGNOSTIC TOOL FOR DIABETES BY USING GLUCOSE SELF-MONITORING DEVICE IN PATIENTS WITH PERIODONTAL DISEASE WITH AND WITHOUT DIABETES - Butt, Farhan; Iqbal, Marium; Hanif, Saima; Ghiraj, M. Mohsin; ., Faisal; Hussain, Mudassir (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the reliability of gingival crevicular blood as a diagnostic tool for diabetes in patients with periodontal disease with and without diabetes. Study Design: Cross sectional study. Place and Duration of Study: Department of Periodontics, Jinnah Medical and Dental College, Karachi, Pakistan, from Jul 2017 to Jul 2018. Methodology: Forty patients with diabetes and 60 patients without diabetes with mild to moderate gingivitis or periodontitis in either the upper or lower anterior region were included. Gingival crevicular blood (GCB) was collected and was assessed by glucometer. The same patient underwent finger stick blood (FSB) and intravenous blood glucose level (IV). Plaque Index (PI), Periodontal Pocket Depth (PPD) and Gingival index were also recorded. Results: A positive correlation (r) was detected between glucose levels of Gingival crevicular blood with finger stick blood with the value of coefficient correlation ‘r’=0.849. The mean values of Gingival index in patients without diabetes is 1.53 ± 0.97mm, patients with newly diagnosed diabetes is 1.87 ± 0.920mm and without diabetes is 2.13± 0.94mm. Conclusion: Blood glucose level can be assessed with the help of Gingival crevicular blood as this technique was found easy and non-invasive to the patient and it can help in diagnosing diabetes during regular periodontal treatment.